The effect of production area on the development of yield producing factors of maize (Zea mays L.) hybrids of different genotypes - Murányi, Eszter (Acta Agraria Debreceniensis, 2016)
Maize yield amount development is determined by the given crop year and the genotype of the applied hybrid, but beside these also by the applied agrotechnical factors, in particular by sowing technology. The development of yield amount and yield producing factors of five maize hybrids of different genotypes has been studied in a small-plot field experiment by the application of different row spacings and plant density variants. The production of the individual plants shows decreasing tendency parallel to the increasing plant density, however, this decrement is compensated by the higher number of plants per unit production area. Individual plant production is determined by the development of yield producing factors, such as the length and the diameter of cobs, just as by the thousand seed weight – that were studied in the present research work as well. In the present research work the decreasing row spacing resulted in a yield increment of 0.67 t ha-1 (4.53%) in 2013, while in contrast in 2014 yield was decreased by 1.75 t ha-1 (14.87%). The high amount of precipitation in March was determinant in 2013: it filled up the soil water stock and balanced the negative effect of the inadequate amount and distribution of precipitation during the vegetation period for the yield. Lower extent of yield increment (0.6 t ha-1) was registered in 2014 in case of the row spacing of 76 cm than in the previous year. In case of a row spacing of 45 cm the difference between the two crop years was 3.1 t ha-1. The highest impact on the yield production factors was found in all treatment combinations in case of the applied hybrid among the three studied treatment factors. In the crop year of 2014 the effect of plant density on cob diameter and thousand seed weight could be revealed as well. In case of the cob diameter significant difference was found between the plant densities of 70 000 and 90 000 plants ha-1, just as between the populations with densities of 50 000 and 90 000 plants ha-1. In case of the thousand seed weight significant differences could be found by the application of plant densities of 70 000 and 90 000 plants ha-1. The highest values of the studied yield producing factors were measured in case of the plant densities of 50 000 and 70 000 plants ha-1; increasing the plant density to 90 000 plants ha-1 resulted in rather decreasing values.